Comparative effectiveness of management options for patients with small renal masses: a prospective cohort study. (9th August 2018) - Alam, Ridwan; Patel, Hiten D.; Osumah, Tijani; Srivastava, Arnav; Gorin, Michael A.; Johnson, Michael H.; Trock, Bruce J.; Chang, Peter; Wagner, Andrew A.; McKiernan, James M.; Allaf, Mohamad E.; Pierorazio, Phillip M.
Abstract : Objectives: To explore the comparative effectiveness of partial nephrectomy (PN), radical nephrectomy (RN), ablative therapies (ablation) and active surveillance (AS) for small renal masses (SRMs; tumour diameter ≤4.0 cm) in the domains of survival, renal function and quality of life (QoL) using the prospectively maintained Delayed Intervention and Surveillance for Small Renal Masses (DISSRM) Registry. Patients and Methods: Estimated glomerular filtration rate (eGFR) was calculated from creatinine values to determine renal function. QoL was measured using the Short Form 12 (SF‐12) questionnaire. The Kaplan–Meier method and Cox proportional hazards regression were used for survival analysis. The mixed‐effects model was used for renal function and QoL analysis. Results: Of 638 patients, 231 (36.2%) chose PN, 41 (6.4%) RN, 27 (4.2%) ablation and 339 (53.1%) AS. Cancer‐specific survival at 7 years was 98.8% in PN patients and 100% in all other groups. Overall survival (OS) at 7 years was 87.9%, 90.2%, 83.5% and 66.1% in PN, RN, ablation and AS patients, respectively. The OS rate was significantly worse in the AS group than other groups and likely attributable to older age and increased comorbidities. The eGFR was lowest in RN patients but comparable in all other groups. QoL was lowest in AS patients due to lower physical health scores, but mental health scores were similar in all groups. Conclusions: With excellent oncological outcomes in all groups, nephron‐sparing approaches, like PN and ablation, are preferred over RN when intervention is indicated for SRMs. AS is a reasonable option for select patients, given the comparable oncological and mental health outcomes.